Justice As Love Hermionitic Study of the Concept of Christian Love in Paul Riccor - Shbani, Monzer (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Paul Riccor, the French philosopher, aims in "Love and Justice" at presenting a new concept of justice, via its relation with love, leaving behind the traditional concept manifested in distributive justice; this concept which was established by Riccor unable to put a finale to the social clash, especially the oppressed and marginalized groups. Hence, he tries to present a new concept of justice via tackling its relation with love. Therefore, this research presents at first the concept of justice as it was presented by Riccor, then proceeds to discuss the discrepancy between the traits of love and justice in accordance with the controversy suggested by Paul Riccor, which will enable us to find a relationship through which justice can be established via gaining back the ability to love, then looking at love as more than a mere individual whim; love as one ethic power capable of making a compromise between happiness and duty. Finally, the research ends up with quite accumulative consequences capable of creating new horizons due to this research.